The I148M PNPLA3 variant mitigates niacin beneficial effects: How the genetic screening in non-alcoholic fatty liver disease patients gains value - Paolini, Erika; Longo, Miriam; Meroni, Marica; Tria, Giada; Cespiati, Annalisa; Lombardi, Rosa; Badiali, Sara; Maggioni, Marco; Fracanzani, Anna Ludovica; Dongiovanni, Paola (Frontiers in Nutrition, 2023)
Background: The PNPLA3 p.I148M impact on fat accumulation can be modulated by nutrients. Niacin (Vitamin B3) reduced triglycerides synthesis in in vitro and in vivo NAFLD models. Objectives: In this study, we aimed to investigate the niacin-I148M polymorphism crosstalk in NAFLD patients and examine niacin’s beneficial effect in reducing fat by exploiting hepatoma cells with different PNPLA3 genotype. Design: We enrolled 172 (Discovery cohort) and 358 (Validation cohort) patients with non-invasive and histological diagnosis of NAFLD, respectively. Dietary niacin was collected from food diary, while its serum levels were quantified by ELISA. Hepatic expression of genes related to NAD metabolism was evaluated by RNAseq in bariatric NAFLD patients (n=125; Transcriptomic cohort). Hep3B and HepG2 cells were silenced (siHep3B) or overexpressed (HepG2I148+) for PNPLA3, respectively. Results: In the Discovery cohort, dietary niacin was significantly reduced in patients with steatosis≥2 and in I148M carriers. Serum niacin was lower in subjects carrying the G at risk allele and negatively correlated with obesity. The latter result was confirmed in the Validation cohort. At multivariate analysis, the I148M polymorphism was independently associated with serum niacin, supporting that it may be directly involved in the modulation of its availability. siHep3B cells showed an impaired NAD biosynthesis comparable to HepG2 cells which led to lower niacin efficacy in clearing fat, supporting a required functional protein to guarantee its effectiveness. Conversely, the restoration of PNPLA3 Wt protein in HepG2I148+ cells recovered the NAD pathway and improved niacin efficacy. Finally, niacin inhibited de novo lipogenesis through the ERK1/2/AMPK/SIRT1 pathway, with the consequent SREBP1-driven PNPLA3 reduction only in Hep3B and HepG2I148M+ cells. Conclusions: We demonstrated a niacin-PNPLA3 I148M interaction in NAFLD patients which possibly pave the way to vitamin B3 supplementation in those with a predisposing genetic background.